China as a factor of international relations (Journal of Oriental Studies, 2017)
In article the priority directions of foreign policy of Kazakhstan and arole of China in foreign policy of our republic are considered. Тhe article isdevoted to the experience of China’s policy in the spheres of internationaleconomy and collective security within such organizations, as ShanghaiCooperation Organization. Is Chinese foreign policy concept in today’s eraof globalization sustainable enough for it to become the world’s secondsuperpower, whish directions form the basis of its promotion. Also, we cansee the analysis of the methods which are used by Chinese government insuch directions like USA, EU, Russia and the evolution of Chinese political,economic and financial relations with major powers of today.